BIOCHEMICAL AND MOLECULAR TAXONOMY OF CHITINOLYTIC CITROBACTER FREUNDII STR. NOV. HARITD11, ISOLATED FROM INDIAN MARINE ENVIRONMENT - HARITHA MERUVU; SRI RAMI REDDY DONTHIREDDY (International Journal of Pharma and Bio Sciences, 2013)
A strain of Citrobacter with chitinolytic activity was isolated by screening of five marine sediment samples near NTPC area of the Visakhapatnam Coast of Bay of Bengal (India), an arm of the Indian Ocean. The taxonomic position of a chitinolytic marine isolate, strain haritD11 was established using a polyphasic approach. The organism merits species status in the genus Citrobacter according to the chemical and phenotypic data. Phylogenetic analysis of the strain based on its 16S rDNA sequence shows that there was 100% similarity and identity without any nucleotide gaps with the species Citrobacter freundii strain DSM 30039(T). As the organism was distinguished with significant differences in certain genotypic and phenotypic characteristics, it was proposed as a new strain variety of Citrobacter freundii and designated as Citrobacter freundii str. nov haritD11 (GenBank accession number of strain D11 is KC344791).